Vegetation Diversity in the Agroforestry System of Kuta Traditional Village, West Java, Indonesia: Vegetation diversity in the agroforestry system of Kuta Traditional Village - Adnan, Bahana Aditya; Erlin, Euis; Dadi; Kurniawati, Tiktiek (Journal of Tropical Life Science, 2026)
This study investigates vegetation diversity within the agroforestry system of Kuta Traditional Village, West Java, Indonesia, a community renowned for its long standing integration of ecological principles and cultural traditions in land management. Twenty plots (20 m × 20 m) were purposively established to assess vegetation structure across four growth stages: trees, poles, saplings, and seedlings. Data collection includes the number of species and the number of individuals of each species, followed by the calculation of the Important Value Index (IVI), Shannon–Wiener diversity index (H′), Margalef species richness index (R), and Pielou’s evenness index (E). Results indicated that Cocos nucifera and Arenga pinnata dominated the mature tree stage, while Coffea canephora prevailed at the pole stage. High diversity (H′ = 2.91–3.41) and richness (R = 5.13–6.23) were observed in trees, poles, and saplings, reflecting balanced community structures and sustainable regeneration. The seedling stage exhibited lower diversity (H′ = 2.67, R = 2.96) despite high evenness (E = 0.96), suggesting selective recruitment patterns. Principal Component Analysis revealed soil pH as the most influential environmental factor shaping species distribution. These findings underscore the importance of traditional agroforestry in sustaining biodiversity, supporting livelihoods, and maintaining ecological resilience, thereby highlighting its significance as a model for sustainable land use and biodiversity conservation in culturally significant landscapes.